Decreased levels of procoagulant phospholipids in bleeding patients treated by vitamin K antagonists. (January 2016) - Mathieu, Emmanuel; Van Dreden, Patrick; Aulagnier, Jérôme; Grusse, Matthieu; Dreyfus, Jean-François; François, Dominique; Vasse, Marc
Summary: International Normalized Ratio (INR) is currently used to monitor vitamin K antagonist therapy, and the bleeding incidence becomes exponential for INR > 4.5. Inversely, more than 50% of patients with a supratherapeutic INR are asymptomatic. Therefore it could be of interest to identify patients with a higher bleeding risk. Microparticles derived from different cell types express procoagulant phospholipids (PPL) which can be evaluated by a chronometric coagulation assay where a shortening of the clotting times is associated with increased levels of PPL. In a series of 174 consecutive patients referred to our Emergency Department with an INR > 5, median level of PPL was significantly (p = 0.004) lower (38.2 s) in the 119 asymptomatic patients than in patients with nonmajor (43.6 s, n = 35) or major bleeding (46.6 s, n = 19), indicating higher levels of procoagulant phospholipids in asymptomatic patients. By receiver operating characteristic curve analysis, a cut-off of 43.5 s discriminated patients with higher haemorrhagic risk (area under the curve = 0.648). In contrast, thrombomodulin levels, quantified either by immunological or functional assays were not significantly different between both groups. In conclusion, evaluation of PPL could be of interest to define the haemorrhagic risk of VKA- treated patients. Highlights: INR is used to monitor vitamin K antagonist (VKA) therapy. More than 50% of patients with an INR > 5 are asymptomatic. Microparticles realised by cell membranes express procoagulant phospholipids (PPL). Asymptomatic patients with INR > 5 have higher levels of PPL than bleeding patients.